Strong and weak cross‐sex correlations govern the quantitative‐genetic architecture of social group choice in Drosophila melanogaster. (13th December 2019) - Geiger, Adam P.; Saltz, Julia B.
Abstract: When genotypes differ in niche‐constructing traits, genotypes are expected to differ in which environments they experience, providing a novel causal relationship between genotypes, environments, and behavior. Such genetic variation in niche construction (or, more precisely, environment construction) is predicted to be especially important for social environments, yet the quantitative‐genetic parameters governing such variation are still poorly understood. Here, we examine genetic variation and cross‐sex genetic correlations for social environment‐constructing behaviors. We focus on whether genetic variation in patch use—the tendency to spend time near food patches where conspecifics may be present—and group‐size preference—the specific group size chosen when individuals are affiliating—is correlated or decoupled across sexes in the fruit fly, Drosophila melanogaster . Across three choice treatments, we find genotype and sex differences in how much time individuals spend near patches, and which group sizes they prefer. We find that the genetic basis of patch use is strongly coupled across sexes, whereas the genetic basis of group‐size preference is completely decoupled across sexes. We discuss how these findings augment and complicate our understanding of the evolutionary genetics of social behaviors.